Active spectral shaping with polarization-encoded Ti sapphire amplifiers for sub-20 fs multi-terawatt systems - Cao Huabao (LASER PHYSICS LETTERS, 2018)
A combination of a polarization-encoded (PE) and a conventional multi-pass amplifier was studied to overcome gain narrowing in the Ti:sapphire active medium. The seed spectrum was pre-shaped and blue-shifted during PE amplification and was then further broadened in a conventional, saturated multi-pass amplifier, resulting in an overall increase of the amplified bandwidth. Using this technique, seed pulses of 44 nm were amplified and simultaneously spectrally broadened to 57 nm without the use of passive spectral corrections. The amplified pulse after the PE amplifier was recompressed to 19 fs. The supported simulations confirm all aspects of experimental operation.